Well, I bet you want your answer right away! So here it is.
<span>Given <span>f (x) = 3x + 2</span> and <span>g(x) = 4 – 5x</span>, find <span>(f + g)(x), (f – g)(x), (f × g)(x)</span>, and <span>(f / g)(x)</span>.</span>
To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
(f – g)(x) = f (x) – g(x)
= [3x + 2] – [4 – 5x]
= 3x + 2 – 4 + 5x
= 3x + 5x + 2 – 4
= 8x – 2
(f × g)(x) = [f (x)][g(x)]
= (3x + 2)(4 – 5x)
= 12x + 8 – 15x2 – 10x
= –15x2 + 2x + 8
<span>\left(\small{\dfrac{f}{g}}\right)(x) = \small{\dfrac{f(x)}{g(x)}}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>g(x)</span></span><span><span>f(x)</span></span><span></span></span></span></span><span>= \small{\dfrac{3x+2}{4-5x}}<span>=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>
My answer is the neat listing of each of my results, clearly labelled as to which is which.
( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span>
Hope I helped! :) If I did not help that's okay.
-Duolingo
</span></span></span></span>
Answer: EQUATION: p-6=-14 ANSWER: p=-8
Step-by-step explanation:
Just simply add 6 to both sides so p can be by by itself. -14+6=-8
Hope this helped you! ^_^
Remember, order of operations
exponent before multiply
so 4x^5/6=4 times x^5/6
simplify the x^5/6 first
remember
![x^\frac{m}{n}=\sqrt[n]{s^m}](https://tex.z-dn.net/?f=x%5E%5Cfrac%7Bm%7D%7Bn%7D%3D%5Csqrt%5Bn%5D%7Bs%5Em%7D)
so
![x^\frac{5}{6}=\sqrt[6]{x^5}](https://tex.z-dn.net/?f=x%5E%5Cfrac%7B5%7D%7B6%7D%3D%5Csqrt%5B6%5D%7Bx%5E5%7D)
so
![4x^\frac{5}{6}=4\sqrt[6]{x^5}](https://tex.z-dn.net/?f=4x%5E%5Cfrac%7B5%7D%7B6%7D%3D4%5Csqrt%5B6%5D%7Bx%5E5%7D)
<span />
Dividing the parallelogram in half and applying trigonometry is the easiest solution for me.